2006
DOI: 10.1523/jneurosci.3264-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cells Do Not Exhibit Unique Migratory or Axonal Growth-Promoting Properties after Spinal Cord Injury

Abstract: Olfactory ensheathing cells (OECs) have been reported to migrate long distances and to bridge lesion sites, guiding axonal regeneration after spinal cord injury (SCI). To understand mechanisms of OEC migration and axonal guidance, we injected lamina propria OECs 1 mm rostral and caudal to C4 SCI sites. One month later, OECs formed an apparent migrating cell tract continuously extending from the injection site through the lesion, physically bridging the lesion. Confocal immunolabeling demonstrated that, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 73 publications
3
84
0
Order By: Relevance
“…If nogo neutralization influences axonal growth, a more likely mechanism of action may be enhanced sprouting of spared projections (41). Similarly, reports that olfactory ensheathing cells promote corticospinal tract regeneration are the subject of uncertainty (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…If nogo neutralization influences axonal growth, a more likely mechanism of action may be enhanced sprouting of spared projections (41). Similarly, reports that olfactory ensheathing cells promote corticospinal tract regeneration are the subject of uncertainty (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The migratory potential of OECs is crucial to their function [16]. However, studies of the migration capacity and behaviour of OECs after transplantation in SCI models have led to contradictory results [17][18][19]. Nevertheless, it has been demonstrated that in injured spinal cord, rat and human OECs migrate for shorter distances, in both rostral and caudal directions, compared to non-injured spinal cords [20].…”
Section: Introductionmentioning
confidence: 99%
“…We should point out that in one study, functional improvement was not observed following OEC transplantation but was observed following Schwann cell transplantation [64]. Moreover, other investigators have not found unique migratory properties of OECs [65] and one report questioned the efficacy of transplantation of lamina propria into complete spinal cord transection [66].…”
Section: Transplantation Of Olfactory Ensheathing Cells Into Experimementioning
confidence: 94%